Primary Pulmonary Lymphoma Presenting with Superior Vena Cava Syndrome in a Young Female - Divya Salhan; Prakash Verma; Tun Win Naing; Ebad Ur Rehman; Saroj Kandel; Danillo Enriquez; Joseph Quist; Frances Schmidt (Case Reports in Pulmonology)
Primary Pulmonary Diffuse Large B Cell Lymphoma (PPDLBCL) is an extremely rare entity, which exhibits an aggressive behavior by compressing local blood vessels. It represents only 0.04% of all lymphoma cases and is extremely rare in young age. We present a case of a primary pulmonary lymphoma with superior vena cava syndrome (SVCS) in a young female. 27-year-old African American female presented with fever, cough, and facial puffiness for 2 weeks and unintentional weight loss. Chest examination showed decreased breath sounds and dullness on percussion on right side. Labs were normal except for mild leukocytosis, high lactate, and lactate dehydrogenase. Chest X-ray showed a large right side infiltrate with pleural effusion but chest CT showed 10 × 14 × 16 cm mass in the right lung without hilar and mediastinal lymphadenopathy. CT guided biopsy of the right lung mass was done and large B cell lymphoma was diagnosed. She received “involved field radiation” because of the bulky tumor size and superior vena cava involvement prior to R-CHOP to which she responded well. PPDLBCL should be considered as one of the differentials in a young patient with a large lung mass, which needs timely diagnosis and management.